Hepatic Clearance of Tissue-Type Plasminogen Activator in Rats - Emeis, J J; van den Hoogen, C M; Jense, D (Thrombosis and Haemostasis, 1985)
The clearance of tissue-type plasminogen activator (t-PA) was studied, in rats, by use of a functional assay for t-PA. Half-lives in the circulation were about one minute both for human (melanoma cell-derived) t-PA and for the rat’s own t-PA. The clearance of t-PA required an intact liver blood flow. In isolated liver perfusion experiments the hepatic extraction of t-PA did not require any plasma proteins, including fast-acting t-PA inhibitor. Competition experiments, using monosaccharides, suggested that known hepatic glycoprotein receptors were not involved in hepatic t-PA extraction.
Keywords: Rat; Tissue-type plasminogen activator; Clearance; Liver; Carbohydrate; Tunicamycin